A Participatory Approach to Uniting the Multiple Agendas of Social Arts - Eltje Bos; Ephrat Huss (Creative Arts in Education and Therapy)
Within rapid global social change and societies becoming ever more diverse, fluid, and divided, the social arts can contribute to maintaining a unified, tolerant, and coherent society. Social arts are often initiated by different stakeholders committed to health, therapy, political action, and/or social change. These are hard to typify and characterize and thus hard to evaluate. This article presents an overview of multiple theories and perspectives in the social arts and suggests how to incorporate them into an evaluative model preserving perspectives and goals of these different stakeholders. We propose a definition of social arts followed by an analysis in the context of fine arts, psychology, and social theories. Next, the challenges of researching and evaluating social arts initiatives are discussed, followed by potential pathways and instruments for assessment. This presentation of frameworks, challenges, and methods may lead to further research on social arts initiatives and their impact on society.